2019
DOI: 10.5505/tbdhd.2019.87587
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Prognosis of Spontaneous Intracerebral Hemorrhage

Abstract: INTRODUCTION: Neutrophil to Lymphocyte Ratio (NLR) is suggested to predict functional outcomes and mortality at admission of patients with intracerebral hemorrhage (ICH). However, effect of timing of NLR measurement on prediction of mortality and expansion in ICH has not been clarified. METHODS: From admission and 24th-hour blood samples, admission NLR (NLR-adm) and 24th-hour NLR (NLR-24th) was calculated as "absolute neutrophil count/lymphocyte count". Hematoma expansion was evaluated with the volume (ABC/2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…16 Many studies have observed similar mechanisms in subarachnoid and intraparenchymal haemorrhages. 17,18 In our study, in line with the findings in the literature, while leukocytosis, neutrophilia and lymphopenia were detected in the stroke group compared with the non-stroke group, a statistically significant increase in the NLR was also found (P < .001).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…16 Many studies have observed similar mechanisms in subarachnoid and intraparenchymal haemorrhages. 17,18 In our study, in line with the findings in the literature, while leukocytosis, neutrophilia and lymphopenia were detected in the stroke group compared with the non-stroke group, a statistically significant increase in the NLR was also found (P < .001).…”
Section: Discussionsupporting
confidence: 92%
“…[10][11][12][13]15,17,18,26 There is not enough evidence to explain the relationship between the NLR values evaluated after the first 24 hours and the patient's clinical situation, and the available evidence is thought to contain bias in many aspects. 10,17,18,26,31…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we excluded 239 duplicates, then an additional 323 studies after screening the titles and abstracts; subsequently, 61 studies remained to undergo full-text review. Finally, we included 26 studies with 7,317 patients in the final analysis ( Lattanzi et al, 2016 , 2017 , 2018 ; Wang et al, 2016 ; Giede-Jeppe et al, 2017 ; Seabra et al, 2017 ; Sun et al, 2017 ; Tao et al, 2017 ; Fan et al, 2018 ; Qi et al, 2018 ; Wang F. et al, 2018 , 2019 ; Zhang et al, 2018a , b , 2019a , b , 2019c ; Guo et al, 2019 ; Pektezel et al, 2019 ; Qin et al, 2019 ; Wang Z. et al, 2019 ; Chen et al, 2020 ; Fonseca et al, 2021 ; Menon et al, 2021 ; Mohamed et al, 2021 ; Radu et al, 2021 ), of which 14 studies reported the prognostic value of NLR for poor outcome, 12 studies reported the prognostic value of NLR for mortality, four studies reported the prognostic value of NLR for hematoma expansion, and three studies reported the prognostic value of NLR for neurological deterioration, respectively.…”
Section: Resultsmentioning
confidence: 99%